Shaping the Transnational Sphere: Experts, Networks and Issues from the 1840s to the 1930s - Davide Rodogno, Bernhard Struck, and Jakob Vogel (Berghahn Books, 2014)
Today the role played by experts, expert knowledge and epistemic communities in international politics is manifest. Decision making in fields ranging from technology to the environment, from science to international security and from European Union integration to economic development is shaped by expert knowledge.1 The politics of expertise are not a new phenomenon. This book examines expert networks and organizations in Europe, in Western Europe in particular, in the period between the mid-nineteenth century and the early 1930s, and demonstrates their relationship with policy-making processes at both the domestic and the international level especially with respect to the social reform movement. The volume explores the activities of networks and non-state actors beyond and below national borders that were particularly important for the dissemination of reform ideas and practices. Social scientists have often neglected the influence of these networks and the circulation of knowledge and expertise, despite the more recent discussions about their ‘Atlantic crossings’ analysed by the historian Daniel T. Rogers.2 The dominance of the paradigm of the nation-state has, until recently, resulted in a focus on intergovernmental and diplomatic relations, and a consequent underestimation of the significance of transnational relations.3 Although the rise of networks of experts has been attributed by social scientists to ‘the birth of a knowledge society’ during the second half of the twentieth century,4 as the chapters in this edited collection demonstrate, the contribution of expert knowledge to policy processes reaches back at least a century earlier. In the mid-nineteenth century, cultural, political, social and economic factors inspired contemporaries to believe in the overarching role of scientific and technological progress as a means to overcome the problems caused by rapid industrialization and social. This book focuses on the transnational sphere as the space where encounters across national borders took place. New ideas were often framed and exchanged within transnational reform networks even though their intended context and purpose were to be found in reform policies at domestic (national) level or in international legislation. Ideas originated in a given place but circulated across national borders were discussed and modified in specific transnational contexts and might shape new legislation in locations at a distance from their origins. The process of transfer encompassed adaptation and modification to specific local or national contexts